Simulating smart grid using a two-layer multiagent framework - Ferreira, Adriano (2017)
The integration of ICT technologies will contribute to meet the objectives of smart grids by applying intelligent strategies to implement their automation functions. The use of the real electrical power energy infrastructure is hardly to be managed. The use of simulation constitutes an alternative to model and test in a simple way these complex power electrical grids, improving the system's reliability, resilience and stability. However, power simulators don't reflect the unpredictable behaviours caused by the collaborative interference of intelligent and cognitive systems, being required an easy and transparent platform to interconnect the intelligent control with the power emulator platforms. This paper introduces a two-layer framework integrating multi-agent-based control systems with power simulator tools, allowing to create a virtual environment to test and simulate the different control strategies and helping the deployment of the future smart grid concept. An instantiation of this framework is deeply analysed for the use of GridLab-D as power simulation tool.